Metabolic Dysfunction Precedes Dopaminergic Loss in Early MSA-C: A Discordant 18F-FDG PET and 99mTc-TRODAT-1 Case Study - Arvian Muhammad Barid; Kharisma Perdani; Trias Nugrahadi; A Hussein S Kartamihardja (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Differentiating early-stage multiple system atrophy-cerebellar type (MSA-C) from other ataxia syndromes presents a significant diagnostic challenge. While striatal dopaminergic denervation is a hallmark of synucleinopathies, it may be absent in the early stages of the cerebellar subtype. This study investigates the temporal dissociation between metabolic and dopaminergic biomarkers. Case Presentation: We report a 48-year-old male presenting with a 5-year history of progressive cerebellar ataxia and mild Parkinsonism, resistant to dopaminergic therapy. Written informed consent was obtained from the patient for the publication of this case details and images. To exclude mimics, a basic metabolic workup and High-resolution 3T MRI were performed. MRI revealed mild cerebellar atrophy but lacked the specific hot cross bun sign. Wilson’s disease screening was negative. Due to limited resources, advanced genetic panels for spinocerebellar ataxias were not performed. The patient underwent dual-modality molecular imaging. On Day 1, 18F-FDG PET/CT demonstrated profound hypometabolism in the cerebellum (Cerebellum/Whole-Brain SUVr: 0.68) and pons (SUVr: 0.72). Conversely, on Day 30, 99mTc-TRODAT-1 SPECT revealed robust, symmetrical striatal uptake with Specific Binding Ratios (SBR) of 1.15 (Right) and 1.12 (Left), indicating preserved presynaptic dopamine transporter density. Conclusion: This case illustrates a critical temporal dissociation in MSA-C pathophysiology: widespread pontocerebellar metabolic failure occurs prior to structural nigrostriatal degeneration. Clinicians must recognize that a normal DAT scan does not exclude MSA-C. In limited-resource settings where genetic testing is unavailable, 18F-FDG PET offers superior sensitivity in the early diagnostic window to support the diagnosis.